Pengembangan Pintu Air Irigasi Pintar berbasis Arduino untuk Daerah Irigasi Manikin - Folkes Eduward Laumal; Edwin P. Hattu; Kusa B. N. Nope (Universitas Syiah Kuala, 2017)
In general, irrigation watergates placed in the Manikin Irrigation Area is supporting tools for agricultural activities that implement a primary–secondary–tertiary channel system. Manikin irrigation watergate is made of iron plates with the certain size which is operated by a move up/down or rotation. This mechanism has led the dissatisfaction service problems in farmers. This study has developed smart irrigation watergate based on Arduino by replacing the lifter/rotator part using DC motor that works automatically based on the Real-time Clock sensor. This sensor sends the data time to Arduino and used as the reference to open or close the watergate. The study used a design method includes interconnecting realtime clock sensors and Arduino, build the programming control, build the DC system on watergates and interconnection to control systems and testing. The test results show that the irrigation watergate moves up and move down every 2 hours based on the data time from the real-time clock, works with a 12-hour time format and operating on 2.7-ampere current.